Art therapy and substance abuse : enabling recovering from alcohol and other drug addiction - Schmanke, Libby (Online access with DDA: Askews (Medicine), 2017)
This book provides art therapists with specific information on substance abuse treatment approaches and explains the bio-psycho-social aspects of addiction. By providing insight into the unique challenges of this client group, it gives art therapists the knowledge and confidence to develop effective interventions for individuals with addictions.